2003
DOI: 10.1038/sj.jhh.1001531
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of multidisciplinary lifestyle intervention for hypertension: a randomised controlled trial

Abstract: Lifestyle factors like weight, alcohol consumption, salt intake and physical activity have shown to be important in treating hypertension. There have been made some randomised trials about the effects of lifestyle interventions, but the numbers of patients have been relatively small and the durations of follow-ups have been short. No controlled trials assessing the effects of lifestyle intervention in a rehabilitation setting have been reported. In this study, the effects of multidisciplinary lifestyle interve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
25
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 29 publications
4
25
0
Order By: Relevance
“…Furthermore, our intervention focused on the effect of lifestyle intervention on hypertension, and a clear effect emerged (15). Its effects on musculoskeletal symptoms were also assessed, because there is evidence that lifestyle factors are among the causes of musculoskeletal symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, our intervention focused on the effect of lifestyle intervention on hypertension, and a clear effect emerged (15). Its effects on musculoskeletal symptoms were also assessed, because there is evidence that lifestyle factors are among the causes of musculoskeletal symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…The recruitment and screening process, as well as the measures for the effect evaluation, have been described earlier in detail (15). Workers were eligible for enrollment in the study if their mean systolic blood pressure (SBP) was 140-179 mm Hg or their mean diastolic blood pressure (DBP) was 90-109 mm Hg or if they were taking antihypertensive medication.…”
Section: Screening and Randomization Of The Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Recent data from intervention trials based on Dietary Approaches to Stop Hypertension show that adopting multiple lifestyle changes may lead to even greater reductions in blood pressure and other cardiovascular risk factors. [3][4][5] Despite the wealth of evidence regarding the benefits of a healthy lifestyle, the available data suggest that adherence to these recommendations among hypertensive patients is poor. For example, participants that reported hypertension from the English Longitudinal Study of Ageing had lower smoking rates but were more likely to report heavy alcohol intake and low physical activity levels compared with normotensives.…”
mentioning
confidence: 99%
“…Work place intervention for the promotion and practice of healthy lifestyle may also be useful. 18 Barriers to uptake of healthy lifestyle also need to be explored for different ethnic groups. The study by Zhao et al 9 also briefly assessed the physician involvement in adoption of healthy lifestyle behaviour by way of receipt of weight loss advice and showed that for obese individuals there does seem to be some differences among ethnic groups.…”
mentioning
confidence: 99%